2017
DOI: 10.1155/2017/9878109
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of an Experimental Steam-Induced Burn Model in Rats

Abstract: Background Most of the current models for experimental burns pose difficulties in ensuring consistency and standardization. Aim of Study We aimed to develop an automated, reproducible technique for experimental burns using steam-based heat transfer. Methods The system developed for steam exposure was based on a novel, integrated, computer-controlled design. Three groups of rats were exposed to steam for 1, 3, and 7 seconds. The lesions were evaluated after 20 minutes, 48 hours, and 72 hours after burn inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…There are further investigations of related studies that indicated the role of substances acting on the imidazoline receptors, on behavior, remembrance, eagerness to learn, locomotor activity and sedation. Finally, progress will also depend on the means of understanding the structural and functional organization of the receptors in the rat cerebral cortex from an interdisciplinary perspective, including psychiatry, psychology, behavioral sciences, genetics, and other neurosciences [8][9][10]. Idazoxan and Efaroxan have a certain potential for being used in new drug development based on the results that have been reported after conducting numerous behavioral animal models, but their clinical use is not implemented yet.…”
mentioning
confidence: 99%
“…There are further investigations of related studies that indicated the role of substances acting on the imidazoline receptors, on behavior, remembrance, eagerness to learn, locomotor activity and sedation. Finally, progress will also depend on the means of understanding the structural and functional organization of the receptors in the rat cerebral cortex from an interdisciplinary perspective, including psychiatry, psychology, behavioral sciences, genetics, and other neurosciences [8][9][10]. Idazoxan and Efaroxan have a certain potential for being used in new drug development based on the results that have been reported after conducting numerous behavioral animal models, but their clinical use is not implemented yet.…”
mentioning
confidence: 99%
“…The mean epithelialization time decreased from 18.23 days in controls, to 14.97 days for TF1,14.77 days for TF-2, 17.55 days for OAQMC, 15.97 days for OAQ (MC+PN), 17.75 days for OAQPG, 16.24 days for OAQ (PG+PN), 15.81 days for OAQ (MC+PG+PN), 14.08 days for O3TF1, 13.79 days for O3TF2 and 18.88 days for GXII, while standard povidone iodine showed the lowest time of 15.50 days.The overall epithelialization time can be presented as: GXII O3TF2. Among the prepared herbal formulations, the blended formulation showed the decrease in epithelization period in comparison with controls, individual extracts and showed comparable results to the standard ointment…”
mentioning
confidence: 84%
“…Burn wounds were created on dorsal part of shaved rat's skin surface using concentrate sulfuric acid, exposed for 10 s. After 24 h, dead tissues were excised using sterile surgical blade through a template designed to produce a third degree burn 14 . All groups were treated same as in excision model.…”
Section: Creation Of Burn Woundmentioning
confidence: 99%
“…Sections (5 mm) were cut and stained with hematoxylin and eosin. The deep II burn (called burn in the following text), which was characterized as a partial deep burn damaging the upper area of the deep reticular dermis and the superficial papillary dermis, 11,12 was confirmed by the pathologic sections ( Fig. 1).…”
Section: Grouping and Treatment Of Animalsmentioning
confidence: 94%